Mucilage‐bound sand reduces seed predation by ants but not by reducing apparency: a field test of 53 plant species. Issue 10 (24th July 2019) - LoPresti, E. F.; Pan, V.; Goidell, J.; Weber, M. G.; Karban, R.
Abstract: Seed mucilage, a coating on seeds or fruit that becomes slimy and sticky when wet, has evolved convergently many times across plants. One common consequence of having seed mucilage is that sand and dirt particles stick to wet seeds and remain tightly bound to the seed surface after the mucilage dries. Here, we test the hypothesis that a mucilage‐bound sand coating protects the seed from seed predators; either as a physical barrier or by reducing apparency of the seed (i.e., camouflage). We experimentally manipulated the sand coating on seeds of 53 plant species of 13 families and assayed the defensive benefit of the sand coating in feeding "depots" near harvester ant nests in California's Central Valley. Consistent with a defensive function, sand coating reduced ant predation on seeds in 48 of the 53 species examined. To test whether this striking benefit was due to reduced apparency, we conducted an addition experiment using flax seeds in which we factorially manipulated the color of both the background substrate and the sand coating, creating visually apparent and unapparent seeds. Our results did not support the reduced apparency hypothesis; seeds coated in background‐matched sand were removed at the same rate as seeds coated in unmatched sand. The defensive benefit of a sand coating was not well‐predicted by seed mass, entrapped sand mass, or sand mass scaled by seed mass. Together, our results demonstrate that seed mucilage is a phylogenetically widespread and effective seed defensive trait and point to the physical barrier, not reduced apparency, as a mechanism.